What shapes the range edge of a dominant African savanna tree, Colophospermum mopane? A demographic approach - Stevens, N (Wiley Open Access, 2021)
Climate is widely assumed to be the primary process that limits the distribution ranges of plants. Yet, savannas have vegetation not at equilibrium with climate, instead its structure and function are shaped by interactions between fire, herbivory, climate, and vegetation. I use the rich literature of a dominant African savanna woody plant, Colophospermum mopane, to demonstrate that climate and disturbance interact with each demographic stage to shape this species range limits. This synthesis highlights that climate-based predictions for the range of C. mopane inadequately represents the processes that shape its distribution. Instead, seed bank depletion and rainfall limitation create a demographic bottleneck at the early seedling stage. The legacy of top-kill from disturbance changes tree stand architecture causing a critical limitation in seed supply. Exposure to top-kill at all demographic stages causes a vigorous resprouting response and shifts tree architecture from that of 1–2 stemmed tall trees to that of a short multi-stemmed shrub. The shorter, multi-stemmed shrubs are below the height threshold (4 m) at which they can produce seeds, resulting in shrub-dominated landscapes that are effectively sterile. This effect is likely most pronounced at the range edge where top-kill-inducing disturbances increase in frequency. The proposed mechanistic, demographic-based understanding of C. mopane's range limits highlights the complexity of processes that interact to shape its range edges. This insight serves as a conceptual model for understanding the determinants of range limits of other dominant woody savannas species living in disturbance limited ecosystems.